CATECHIN: A TLR4 MEDIATED CHAIN BREAKING INHIBITOR OF SIGNALLING CASCADE IN ENDOTOXIN-INDUCED LIVER INJURY: Life Sciences-lmmunobiology - PRAVEEN RISHI; SUSHMA BHARRHAN; SALONY VERMA; SATISH K. PANDEY; SUMEHA ARORA; RUPINDER TEWARI (International Journal of Life Science and Pharma Research, 2022)
In view of the limitations of the existing therapy, the present study was carried out in order to evaluate the potential of catechin as a natural polyphenolic inhibitor against endotoxin-induced liver injury in a rat model. The levels of liver function enzyme markers, histological architecture, expression of signalling molecules involved in endotoxin mediated signalling pathway, levels of hepatic oxidative markers and antioxidants were analyzed in both endotoxin (10 mg/kg body weight injected intraperitoneally) challenged rats and the rats supplemented with kitchen for 15 days (50 mg/kg body weight administered orally) prior to endotoxin challenge. Oral supplementation of catechin for fifteen days followed by challenge with endotoxin decreased the levels of liver enzyme markers, nitrite and lipid peroxidation along with an increase in hepatic antioxidant activity. Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) analysis revealed the inhibition of expression of CD14, TLR4, MD2, MyD88 and IL-12B (p40) by catechin supplementation. The results of these biochemical and molecular studies correlated well with the histological alterations with once as well as earlier findings. It may be inferred from the study that catechin is able to inhibit the signalling cascade starting with the downregulation of the extrinsic molecules such as CD14, TLR4, MD2 and MyD88 and further going downstream to intrinsic molecules such as IL-12B, along with upregulation of antioxidant profile. Thus, catechin may be considered as a chain breaking inhibitor of the signalling cascade involved in endotoxin mediated liver damage and may serve as an immunomodulator to prevent endotoxin-mediated hepatotoxicity.